Термозалежне накопичення флавоноїдів інтродукованими за полярне коло деревними рослинами - Kalacheva, N.V.; Zhiboedov, P.M.; Kashulin, Р.А.; Zhirov, V.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2001)
The character of flavonoids accumulation in arboreal plants introduced in Kola Subarctic and cultivated under various hydrothermal conditions is investigated. The high sensitivity of flavonoid pool to mainly temperature conditions of environment is found.